Zinc oxide : production, properties and applications - Galvan, Carmen (Chemistry research and applications series., 2020)
"In Zinc Oxide: Production, Properties and Applications, the authors first provide a summary of the natural sources available for the synthesis of zinc oxide nanoparticles, enlisting some plant-mediated synthesized zinc oxide nanoparticles showing promising antimicrobial, antioxidant, cytotoxic and photocatalytic properties. Important technological opportunities and challenges emphasizing the electrical and optoelectronic features of elongated zinc oxide nanoparticle nanosystems are reviewed. The various nonlinear optical phenomenon observed in zinc oxide thin film, including nonlinear absorption, nonlinear refraction, nonlinear scattering and harmonic generations are introduced. Selected literature on the use of zinc oxide nanoparticles for the immobilization of enzymes is reviewed, as well as the use of zinc oxide nanoparticle/enzyme systems in the fabrication of biosensors. The authors explore transition metal doped zinc oxide nanoparticles for a wide range of catalytic organic reactions, further exploring their catalytic applications for organic transformations at mild reaction conditions. The basic concepts behind the development of nanostructured zinc oxide nanoparticles, including the solid state reaction, hydrothermal method, solvothermal method and co-precipitation method are discussed. Lastly, a facile, eco-friendly synthesis of zinc oxide nanoparticles using the peel extract of Musa paradisiaca L, Punica granatum L, and Citrus reticulata Blanco as bioreducing agent is reported"--